Pengaruh Current Ratio dan Debt to Assets Ratio terhadap Return on Asset pada Perusahaan Subsektor Makanan dan Minuman - Fifi Afiyanti Tripuspitorini; Hasbi Assidiki Mauluddi; Wika Hasna Asyifa (Jurnal Accounting Information System (AIMS), 2022)
This study aims to determine the effect of Current Ratio (CR) and Debt to Assets Ratio (DAR) on Return on Assets (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The population in this study were 18 companies, using purposive sampling technique, in order to obtain 10 food and beverage companies listed on the BEI that met the criteria, namely companies that were not delisted and always published financial reports that could be accessed during the observation period. The data source used is secondary data in the form of company financial statements for four years, 2016 - 2019. The research method used is associative with a quantitative approach. The panel data regression test was assisted by using Eviews 9. The panel data regression method chosen was the Common Effect Model. The results showed that CR had a significant positive effect on ROA, but DAR had no effect on ROA. CR and DAR affect ROA simultaneously and significantly.